Application of the Crystallo-Calorific Hardening approach to the constitutive modeling of the dynamic yield behavior of various metals with different crystalline structures. (November 2017) - Francart, Charles; Demarty, Yaël; Bahlouli, Nadia; Ahzi, Saïd
Highlights: Dynamical experimental characterization of mechanical behavior of 6 different metallic materials. Determination of the unique sets of parameters of the CCH models for each material. Validation of the modeling designed of each material using the CCH approach. Commentaries on the yield behavior of each material. Abstract: The Crystallo-Calorific Hardening (CCH) constitutive approach, aims to formulate the yield behavior of metals by taking into account different lattice structures (FCC, BCC and HCP). Such physically-based models have been developed to provide accurate predictive tools over wide ranges of temperatures and strain rates and especially for impact applications. In this work, these models are numerically implemented for application to numerous industrial well-known metals with different lattice structures (Cu-a1 copper, pure Molybdenum, AZ31B-O magnesium alloy, Ti-6Al-4V titanium alloy and 36-NiCrMo-16 (AISI4340) austenitic steel). To identify the models parameters and to compare our predicted results to experimental ones, we also performed experimental tests, namely uniaxial compression tests under both quasi-static and dynamic loadings rates. The determined unique sets of parameters of the CCH models are provided in this paper for each considered material. The modeling of each considered material is carefully explained and the comparisons between experimental results and CCH model predictions are thoroughly discussed.